THE IMMUNOLOGICAL ROLE OF ANTI-H. PYLORI ANTIBODIES LEVEL, INF-Γ, AND TNF-Α IN A NUMBER OF PATIENTS WITH A TUMOR IN THE DIGESTIVE SYSTEM IN BABYLON GOVERNORATE - Jaafar , Salim Shamkhi; Jabber , Ehab Y.; Alwish , Amer Abdul Husain; Al- Mammori , Raheem Tuama Obayes; Shareef , Hasanain Khaleel (Antis-Publisher, 2024)
General Background: Helicobacter pylori is a well-known bacterium responsible for chronic infections, significantly contributing to gastric and mucosa-associated lymphoid tissue cancers, as well as peptic ulcer disease. Specific Background: The link between H. pylori infection and gastrointestinal (GIT) tumors remains under-explored, particularly concerning immunological parameters. Knowledge Gap: The role of immune markers, such as anti-H. pylori IgG antibodies, TNF-α, and IFN-γ, in distinguishing between malignant and benign GIT tumors is unclear. Aims: This study aimed to assess the relationship between H. pylori infection and immunological factors in patients with malignant and benign GIT tumors, as well as controls, using serum levels of Anti-H. pylori IgG, TNF-α, and IFN-γ. Results: The study included 100 serum samples from patients with malignant (n=40) and benign (n=35) GIT tumors, irritable bowel disease (IBD) controls (n=15), and healthy controls (n=10). The results revealed significantly elevated levels of anti-H. pylori IgG in patients with malignant tumors compared to those with benign tumors, IBD controls, and healthy controls. Male patients had higher anti-H. pylori IgG levels than females. Elevated levels of TNF-α and IFN-γ were also observed in patients with malignant tumors, correlating with higher anti-H. pylori IgG levels. Novelty: This study highlights the association between elevated H. pylori IgG antibodies and increased TNF-α and IFN-γ levels in malignant GIT tumors, particularly in males, suggesting H. pylori's role in cancer progression. Implications: The findings suggest that early detection of elevated anti-H. pylori IgG and inflammatory cytokines could improve the diagnosis and management of GIT malignancies, especially in male populations. Further research on a larger cohort is recommended to explore the mechanisms driving this relationship.